Intraoperative high-field magnetic resonance imaging, multimodal neuronavigation, and intraoperative electrophysiological monitoring-guided surgery for treating supratentorial cavernomas - Fang-ye Li (KeAi Communications Co., Ltd., 2016)
Objective: To determine the beneficial effects of intraoperative high-field magnetic resonance imaging (MRI), multimodal neuronavigation, and intraoperative electrophysiological monitoring-guided surgery for treating supratentorial cavernomas. Methods: Twelve patients with 13 supratentorial cavernomas were prospectively enrolled and operated while using a 1.5 T intraoperative MRI, multimodal neuronavigation, and intraoperative electrophysiological monitoring. All cavernomas were deeply located in subcortical areas or involved critical areas. Intraoperative high-field MRIs were obtained for the intraoperative âvisualizationâ of surrounding eloquent structures, âbrain shiftâ corrections, and navigational plan updates. Results: All cavernomas were successfully resected with guidance from intraoperative MRI, multimodal neuronavigation, and intraoperative electrophysiological monitoring. In 5 cases with supratentorial cavernomas, intraoperative âbrain shiftâ severely deterred locating of the lesions; however, intraoperative MRI facilitated precise locating of these lesions. During long-term (>3 months) follow-up, some or all presenting signs and symptoms improved or resolved in 4 cases, but were unchanged in 7 patients. Conclusions: Intraoperative high-field MRI, multimodal neuronavigation, and intraoperative electrophysiological monitoring are helpful in surgeries for the treatment of small deeply seated subcortical cavernomas. Keywords: Cavernoma, Intraoperative electrophysiological monitoring, Intraoperative magnetic resonance imaging, Multimodal neuronavigation